2007
DOI: 10.1007/bf03022659
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuates intestinal mucosa injury induced by intestinal ischemia-reperfusion in the rat

Abstract: Purpose:We investigated whether propofol at a sedative dose can prevent intestinal mucosa ischemia/reperfusion (I/R) injury, and if propofol can attenuate oxidative stress and increases in nitric oxide (NO) and endothelin-1 (ET-1) release that may occur during intestinal I/R injury. Methods:Rats were randomly allocated into one of five groups (n = 10 each): (i) sham control; (ii) injury (one hour superior mesenteric artery occlusion followed by three hours reperfusion); (iii) propofol pre-treatment, with propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 43 publications
4
44
1
3
Order By: Relevance
“…The intestinal I/R injury was associated with dramatic increases in MDA level and MPO activity and decrease in SOD activity (31). In the present study, SOD activity in the I/R group was signifi cantly lower than in the sham group (p < 0.05).…”
Section: Table 3 the Effects Of Exercise On Intestinal Tissue Injurycontrasting
confidence: 42%
See 1 more Smart Citation
“…The intestinal I/R injury was associated with dramatic increases in MDA level and MPO activity and decrease in SOD activity (31). In the present study, SOD activity in the I/R group was signifi cantly lower than in the sham group (p < 0.05).…”
Section: Table 3 the Effects Of Exercise On Intestinal Tissue Injurycontrasting
confidence: 42%
“…Increased concentrations of MDA indicate a degree of lipid peroxidation confi rming the oxidative damage in intestinal tissues. In experimental studies with I/R models (29,31,32), MDA levels in intestinal tissue were found to be signifi cantly higher in I/R group compared to sham and treatment groups. A prior study (28) also showed that the MDA level in intestinal tissues in rats subjected to exercise tests was signifi cantly lower than that in sham group.…”
Section: Table 3 the Effects Of Exercise On Intestinal Tissue Injurymentioning
confidence: 94%
“…Free radical-mediated oxidation of proteins results in the formation of carbonyl groups in quantities that reflect the intensity of the oxidative stress 1,3 . Oxidant stress is one of major factor contributing to intestinal I/R injury 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Propofol, characterized by a phenolic structure similar to α-tocopherol, provides an enhancement in antioxidant efficacies and erythrocytes protection against oxidative damage that have been demonstrated both in vitro and in vivo 7,15,16,17 . NAC, an attractive drug which has few side-effects, counteracts oxidative stress in many studies concerning I/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation